2018
DOI: 10.1038/s41419-018-0863-8
|View full text |Cite
|
Sign up to set email alerts
|

A fully defined static suspension culture system for large-scale human embryonic stem cell production

Abstract: Human embryonic stem cells (hESCs) play an important role in regenerative medicine due to their potential to differentiate into various functional cells. However, the conventional adherent culture system poses challenges to mass production of high-quality hESCs. Though scientists have made many attempts to establish a robust and economical hESC suspension culture system, there are existing limitations, including suboptimal passage methods and shear force caused by dynamic stirring. Here, we report on an effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 56 publications
(65 reference statements)
0
12
0
2
Order By: Relevance
“…Previous studies with mouse ESCs reported that the differential upregulation of pluripotent markers in 3-D culture was dependent on scaffold composition and stiffness [34,58]. A recent study using single cell inoculation and the expansion of human ESCs in large-scale bioreactors resulted in the maintenance of OCT4 levels but the upregulation of SOX2 in 3-D grown ESC aggregates [59]. In another study, a 3-D culture of H9 clumps in VS functionalized PEG scaffolds resulted in upregulated gene expression of SOX2 and KLF4 but not OCT4 and NANOG when compared to 2-D cultured cells [52].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies with mouse ESCs reported that the differential upregulation of pluripotent markers in 3-D culture was dependent on scaffold composition and stiffness [34,58]. A recent study using single cell inoculation and the expansion of human ESCs in large-scale bioreactors resulted in the maintenance of OCT4 levels but the upregulation of SOX2 in 3-D grown ESC aggregates [59]. In another study, a 3-D culture of H9 clumps in VS functionalized PEG scaffolds resulted in upregulated gene expression of SOX2 and KLF4 but not OCT4 and NANOG when compared to 2-D cultured cells [52].…”
Section: Discussionmentioning
confidence: 98%
“…OCT4 expression, which ranged from a slight decrease reported in thermoresponsive synthetic hydrogels [52], to no significant change in natural scaffolds composed of hyaluronic acid [30], chitosan or alginate [53]. However, upregulation of select core pluripotent markers has been observed in 3-D culture of mouse [36,54] as well as human ESCs [55,56], suggesting a dependence on scaffold composition and culture conditions. We have reported upregulation of select naïve pluripotent markers in primed [37] and naïve human ESCs In both mouse and human ESCs, focal adhesion and integrin signaling serve pleiotropic roles in anchorage, contractility, survival, proliferation as well as support or inhibition of self-renewal [63].…”
Section: Discussionmentioning
confidence: 99%
“… Gu et al, 2017 , Li et al, 2018 , Liu et al, 2018 , ISO 20387, 2018 , Tan et al, 2018 , Wang et al, 2015 , Wang, et al, 2019 , Wang et al, 2018 .…”
Section: Uncited Referencesmentioning
confidence: 99%